Axial compressive behavior of partially CFRP confined seawater sea-sand concrete in circular columns – Part I: Experimental study. (15th August 2020) - Yang, Junlong; Wang, Jizhong; Wang, Ziru
Abstract: Due to the extraordinary corrosion resistance of fiber-reinforced polymer (FRP), the use of seawater sea-sand concrete (SSC) combined with FRP materials becomes highly attractive in the constructions of coastal and marine infrastructures. To this end, a total of 40 CFRP confined seawater sea-sand concrete cylinders are constructed and tested under axial compressive load in this study. The main variables of the test include the concrete type, CFRP strengthening schemes and the number of CFRP layers. The failure modes, axial stress-strain curves, lateral strain-axial strain relationships and CFRP hoop strain distributions of the specimens are analyzed systematically. It can be detected from the test results that both unconfined and CFRP confined SSC exhibited similar mechanical properties compared with the corresponding specimens cast with normal concrete. Moreover, the clear spacing ratio and the confinement stiffness of CFRP were found to be the two most important factors in accounting for the axial compressive behaviors and the dilation properties. Finally, a new stress-strain model proposed in this paper and several existing models were used to predict the ultimate conditions of CFRP partially wrapped columns in this test. The accuracy and reliability of each model were verified and discussed by comparing the test observations and theoretical predictions.